A comparative study of Malay and Chinese child-rearing practices / Gan Muih Huei - Gan, Muih Huei (1977)
Much of the literature on child rearing practices in Malaysia, over the past decades have tended to concentrate on the rural Malays. Although much has been written on the Chinese in Malaysia, there is a dearth of studies on Chinese socialization practices. In view of the rapid urbanization, economic development and social changes, Malaysia is undergoing, there is need for information on urban communities that keep pace with these changes. The purpose of the study is to investigate patterns of child rearing practices among the Malays and Chinese middle class living in an urban setting. Forty mothers of Standard 1 boys and girls were interviewed in their homes to obtain information on biographical and other home background data and variables relating to child rearing practices. The findings indicated that there were few differences in educational aspiration, independence training, early nurturance variable; but, on measures such as permissiveness and restrictions, discipline and sociability. No marked race differences in sex-role differentiation were noted, however, in both groups, boys and girls differ in their choice of toys and games (eg, girls play with dolls, kitchen sets and boys with gun, soldiers and so on). The similarities among the Chinese and Malays in this study, will be discussed in the light that the parents were highly comparable in terms of education level and medium and other home background variables. By and large, the present findings were found to lend support to those others. Nevertheless, the present study implied that future research involving larger and more representative samples are needed before firm conclusion can be reached.